Preliminary report for zircon geochronology of tonalitic gneiss at an unnamed nunatak in western part of the Napier Complex, East Antarctica - Horie, Kenji; Takehara, Mami; Hokada, Tomokazu; Baba, Sotaro; Kamei, Atsushi; Kitano, Ippei; Nantasin, Prayath; Setiawan, Nugroho; Dashbaatar, Davaa-ochir; Motoyoshi, Yoichi (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object